Characterization of underutilized fruit crops: bael and karonda by RAPD marker (Indian Journal of Arid Horticulture, 2025)
Twenty four accession of Bael, representing four cultivars (Pant Shivani, Pant Urvashi, Pant Sujata and Pant Aparna) and seven accessions of Karonda, representing three cultivars (Pant Manohar, Pant Sudarsan, and Pant Suvarna) have been characterized with RAPD markers. In case of Bael out of the 19 primers screened, 5 were amplified reproducible bands and only three primers were selected for polymorphic study. Out of 10 DNA fragments amplified with three random primers, 8 showed polymorphism. These genotypes were classified into two major groups with each containing three sub- groups. While, in Karonda out of the 19 primers screened, 4 primers amplified reproducible bands and only two primers were selected for the polymorphic study. Out 10 DNA fragments amplified with two random primers, 7 were polymorphic. These genotypes were grouped into two major clusters and one cluster containing two sub- clusters while other consists only one cluster. RAPD data were analyzed by cluster analysis and UPGMA Our analysis revealed that in Bael, some genotypes are identical at DNA level but given different name whereas, Karonda genotypes showed the existence of considerable variation among the test accessions.
Keywords: Bael Germplasm; Karonda; RAPD; DNA; Dendogram